2021
DOI: 10.1017/s1092852921000316
|View full text |Cite
|
Sign up to set email alerts
|

Neurochemistry of response inhibition and interference in gambling disorder: a preliminary study of γ-aminobutyric acid (GABA+) and glutamate–glutamine (Glx)

Abstract: Objective. Neurobehavioural research on the role of impulsivity in gambling disorder (GD) has produced heterogeneous findings. Impulsivity is, however, a multifaceted construct, with different experimental tasks measuring different sub-processes, such as response inhibition and distractor interference. Little is known about the neurochemistry of inhibition and interference in GD.Methods. We investigated response inhibition with the Stop Signal Task (SST) and distractor interference with the Eriksen Flanker Tas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 66 publications
(157 reference statements)
0
0
0
Order By: Relevance
“…Put simply, the role of Glx, glutamate in particular, is to trigger neurons to release neurotransmitters and is a major excitatory transmitter in the brain (Zhou & Danbolt, 2014). Weidacker et al (2022) found no correlation between the ACC GABA or Glx in the ability to stop on a stop-signal task. However, they found that ACC Glx positively correlated with errors in Go conditions in a stop-signal task.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…Put simply, the role of Glx, glutamate in particular, is to trigger neurons to release neurotransmitters and is a major excitatory transmitter in the brain (Zhou & Danbolt, 2014). Weidacker et al (2022) found no correlation between the ACC GABA or Glx in the ability to stop on a stop-signal task. However, they found that ACC Glx positively correlated with errors in Go conditions in a stop-signal task.…”
Section: Discussionmentioning
confidence: 90%
“…Response inhibition and interference task performance are assumed to depend on optimally balancing excitatory and inhibitory neurometabolites (Krause et al, 2013;Weidacker et al, 2022). γ-aminobutyric acid (GABA) is a well-known neuro-metabolite and is involved in maintaining optimal behavioural performance.…”
Section: Chapter 3: Magnetic Resonance Spectroscopy: Video Game Use A...mentioning
confidence: 99%
See 3 more Smart Citations